2017
DOI: 10.3390/su9010121
|View full text |Cite
|
Sign up to set email alerts
|

Biochars as Potential Adsorbers of CH4, CO2 and H2S

Abstract: Methane gas, as one of the major biogases, is a potential source of renewable energy for power production. Biochar can be readily used to purify biogas contaminants such as H 2 S and CO 2 . This study assessed the adsorption of CH 4 , H 2 S, and CO 2 onto four different types of biochars. The adsorption dynamics of biochars were investigated in a fixed-bed column, by determining the breakthrough curves and adsorption capacities of biochars. The physicochemical properties of biochars were considered to justify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…Carbon dioxide and N 2 O emissions resulted in no significant difference over any of the trials. The lack of reduction in emissions of CH 4 is in agreement with Sethupathi et al [30], where it was reported that tested biochar capacities to adsorb CH 4 were little to none. Sethupathi et al [30] also reported the CO 2 adsorption capacity for the same biochar discussed earlier in regards to H 2 S adsorption, with a low capacity when tested as a mix of gases.…”
Section: Treatment Effects On Greenhouse Gasessupporting
confidence: 80%
See 3 more Smart Citations
“…Carbon dioxide and N 2 O emissions resulted in no significant difference over any of the trials. The lack of reduction in emissions of CH 4 is in agreement with Sethupathi et al [30], where it was reported that tested biochar capacities to adsorb CH 4 were little to none. Sethupathi et al [30] also reported the CO 2 adsorption capacity for the same biochar discussed earlier in regards to H 2 S adsorption, with a low capacity when tested as a mix of gases.…”
Section: Treatment Effects On Greenhouse Gasessupporting
confidence: 80%
“…The lack of reduction in emissions of CH 4 is in agreement with Sethupathi et al [30], where it was reported that tested biochar capacities to adsorb CH 4 were little to none. Sethupathi et al [30] also reported the CO 2 adsorption capacity for the same biochar discussed earlier in regards to H 2 S adsorption, with a low capacity when tested as a mix of gases. This low CO 2 adsorption capacity in the presence of other gases equates to <1 h before the biochar's capacity is reached under conditions observed in this study at all biochar doses.…”
Section: Treatment Effects On Greenhouse Gasessupporting
confidence: 80%
See 2 more Smart Citations
“…Pine biochar contains more carboxyl groups and fewer oxygen groups, which confirms the assumption that this biochar is a suitable material for immobilizing of microorganisms in pores and on the surface of biochar. Scientists have investigated the use of a biochar additive made of various plant species for adsorbing CH 4 , CO 2 and H 2 S from single gases and multi‐component gas mixtures . The studies have shown that the considered biochar additive has the highest capacity of adsorbing CO 2 and H 2 S, while its capacity of adsorbing CH 4 is the lowest in the case of adsorption from single (pure) gases.…”
Section: Resultssupporting
confidence: 80%